?IMPERATA CYLINDRIC A (LINN.) P. BEAUV AFFECTS GERMINATION, EARLY GROWTH AND CELL DIVISION AND DEVELOPMENT IN SOME CROP SPECIES (Biological Sciences - PJSIR, 1994)
Imperaia cylindrlca (Linn.) P. Beauv., is a troublesome grass that may exclude associated species from common habitat. Laboratory studies indicated that the aqueous extracts, rain leachates and litter from shoots and rhizomes sup- pressed either germination, seedling growth or both of mustard (Brassica campestris], Bajra (Pennisetum americanum) and letuce (Lactuca Saliva). The percentage of dividing cells and their sizes in root tips of test species were small under test condition. Rain leachates contained caffeic,p-coumaric,p-hydroxy-benzoic, syringic, chiorogenic, iso-chlorogenic, ferulic and vanillic acids and scopolin and scopoletin. The findings suggest that the decreased radicle growth may have resulted from inhibition of cell division and development. The observed aggression of'fhis species may be attributable at least in parts to its allelopathic influences.